Sistem Informasi Pengelolaan Data Simpan Pinjam Koperasi - sukadi sukadi (LPPM Universitas Merdeka Madiun, 2025)
This researchhis motivated by the large number of cooperativessin Indonesia, consisting of consumerccooperatives, producer cooperatives, serviceecooperatives, savings and loan cooperatives, and also multi-purpose cooperatives (KSU) [3]. Where one of the functions of cooperatives is to develop theepotential and economic capabilities of members and the community. In carrying out its activities, of course, cooperatives need a system to process their data. This research aims to create a system design for processing savingssand loan data in savings and loan cooperatives or multi-purpose cooperatives. The researchhmethod used is the SystemnDevelopment Life Cycle (SDLC) waterfall method. This SDLC waterfall is one of the modeling of the SDLC method which is systematic or measurable from the initialsstage to the finalsstage. The results of this study can be used as a reference in creating a system for processing savings and loan data in savings and loan cooperatives and also multi-purpose cooperatives, although in creating the system the number of tables used may be different in each savings and loan cooperative and also multi-purpose cooperative